ความสวยงามวางนัยทั่วไป : ผลคูณของจำนวน 143 กับจำนวนเต็มบวกที่หารลงตัวด้วยจำนวนที่ทุกหลักเป็นเลขโดด 7(Generalized Beauty: the Product of the Number 143 and the Positive Integer Divided by the Number That Every Digit as 7) - ดั้นเมฆ, ดาราวรรณ; เอี่ยมพันธ์, อัยเรศ (Science Essence Journal, 2012)
บทความนี้นำเสนอการศึกษาและการหารูปแบบทั่วไปของผลคูณของจำนวน กับจำนวนเต็มบวกที่หารลงตัวด้วยจำนวนที่ทุกหลักเป็นเลขโดด โดยทฤษฎีบทที่ใช้เป็นเครื่องมือหลักในการพิสูจน์ คือหลักการอุปนัยเชิงคณิตศาสตร์ รูปแบบทั่วไปของผลคูณของจำนวน กับจำนวนเต็มบวกที่หารลงตัวด้วยจำนวนที่ทุกหลักเป็นเลขโดด ที่ได้นั้นจะขึ้นอยู่กับจำนวนของเลขโดด โดยแบ่งได้เป็นสามกรณี คือจำนวนของเลขโดด เท่ากับหนึ่ง สอง และมากกว่าหรือเท่ากับสาม This article presents the study and finding a general form of the product of the number and the positive integer divided by the number that every digit as . The main theorem for proof is the Principle of Mathematical Induction. The general form of the product of the number and the positive integer divided by the number that every digit as is depended on the number of which is divided into three cases: the number of is one, two, greater than or equal to three. <p class="MsoNormal" style="text-justify: inter-cluster; text-align: justify; line-height: 18pt; margin: 0in 0in 0pt; vertical-align: baseline; tab-stops: 30.0pt; mso-pagination: none; mso-layout-grid-align: none;">